In vitro antidiabetic and advanced glycation end products inhibitory activity of methanol extracts of various Dendrobium species - Thaniwan Cheun-Arom, Boonchoo Sritularak (Journal of Applied Pharmaceutical Science, 2023)
Dendrobium orchids are one of the most varied species. In traditional Chinese medicine, Dendrobium has been reported to have an antidiabetic effect and has been used in the preparation of herbal medicines for a long time. This study aimed to investigate the in vitro antidiabetic (α-amylase and α-glucosidase assay) activities and advanced glycation end products (AGEs) inhibitory activity of the methanol extracts of 20 Dendrobium species. Phytochemical constituents and total phenolic and total flavonoid contents of the extracts were evaluated, as well. The total phenolic content was exhibited to be in the range of 31.73–132.70 mg GAE/g, and total flavonoid content was found in the range of 58.80–237.57 mg QE/g. The highest inhibitory activity of α-amylase was reported in D. parishii Rchb.f. (IC50 46.57 μg/ml. The most effective inhibitory activity of α-glucosidase was found in D. ellipsophyllum Tang & Wang. (IC50 128.69 μg/ml) and D. brymerianum Rchb.f. (IC50 138.27 μg/ml). Dendrobium brymerianum Rchb.f. and D. scabrilingue Lindl. were shown to have the most potent inhibited AGEs formation with IC50 values of 34.44 and 46.95 μg/ml, respectively, compared to aminoguanidine (IC50 49.81 μg/ml). As a result, several Dendrobium species displayed strong antidiabetic and AGEs inhibitory activity, and they have the potential for further development.
Keywords: Dendrobium orchids, phytochemical, antidiabetic, Þ-glucosidase, Þ-amylase, advanc